Influence of Eastern Pacific Hurricanes on the Southwest US Wildfire Environment - Karthik Balaguru; Sally S.‐C. Wang; L. Ruby Leung; Samson Hagos; Bryce Harrop; Chuan‐Chieh Chang; Sandro W. Lubis; Oluwayemi A. Garuba; Sourav Taraphdar (Geophysical Research Letters, 2024)
Abstract While some previous studies examined the contribution of Eastern Pacific (EP) hurricanes toward precipitation in the arid Southwest US (SWUS), their potential to influence wildfires in that region has not been explored. Here we show, using observations and simulations from the Energy Exascale Earth System Model (E3SM), that recurving EP hurricanes modulate the wildfire environment in the SWUS by increasing precipitation and soil moisture, and reducing the vapor pressure deficit. This is especially the case during late season months of September–October when the likelihood of storms to recurve and make landfall increases. Further, analysis of burnt area observations reveals that for the months of September–October, recurving EP hurricanes may significantly reduce the prevalence of wildfires in the SWUS. Finally, E3SM simulations indicate that late season EP hurricanes have been on the decline, with important implications for wildfires in the SWUS.